Edukasi Perancangan Media Pembelajaran Bebasis Android - Yusdarina - -; Syamsuriana Basri; Agussalim Agussalim (PPM LP2M UIN Alauddin Makassar, 2022)
This service focuses on research on designing educational media based on Android applications, one of the alternative media that is developing in this era of information openness and in accordance with the increasing circulation of smartphones. The implementation of Community Service aims to educate subject teachers, especially at SMK Muhammadiyah Bungoro, in making or designing Android-based learning media. This service activity is carried out through several stages consisting of stages 1) determining the needs of partners which include observation, grouping, and Determining the Implementation of Activities, Stage 2) education and Assistance and Stage 3) Evaluation. With this service activity, teachers become more technologically literate, add variety to learning, and create innovative learning and attract students' interest in learning. The use of technology in learning will make it easier for teachers to convey material because now technology is no longer new to students, they are already familiar and proficient in using technology. Through this service activity the participants were able to design android-based learning media so that their pedagogical abilities increased.